Relationship Between Oxytocin Massage and Breast Milk Production in Post-Term Mothers at Mopuya Community Health Center - Fitrianti Rahayu; Widia Shofa Ilmiah; Rizful Maulina (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Optimal breast milk production is essential for supporting infant health and development, especially during the first months of life. One non-pharmacological method that has been shown to help increase breast milk production is oxytocin massage. This technique stimulates the release of the hormone oxytocin, which plays a vital role in triggering the let-down reflex, thereby facilitating the flow of milk from the mammary glands. The purpose of this study was to examine the relationship between oxytocin massage and breast milk production among postpartum mothers at Mopuya Community Health Center. This research employed an observational analytical design with a cross-sectional approach. A total of 25 postpartum mothers were recruited as respondents using purposive sampling. Data collection was conducted through surveys and direct observations, followed by statistical analysis using Kendall’s tau_b non-parametric correlation test. The results showed a strong and statistically significant correlation between oxytocin massage and breast milk production, with a correlation coefficient of 0.699 and a p-value of 0.000 (p < 0.05). This indicates that mothers who received regular oxytocin massage tended to have better milk production compared to those who did not. The findings highlight oxytocin massage as an effective, simple, and safe non-pharmacological intervention that can be implemented in maternal and child health services to support breastfeeding success. Given its benefits, healthcare providers, especially midwives and lactation counselors, are encouraged to educate and train postpartum mothers in oxytocin massage techniques. Further research with larger sample sizes and varied settings is recommended to strengthen evidence and explore long-term impacts on breastfeeding duration and infant growth.